The recepetion of Peter singer´s theories in France - Emilie Dardenne (Ethic@: an International Journal for Moral Philosophy)
Peter Singer’s views on the status of animals, the sanctity of human life, and world poverty have attracted both attention and intense controversy in many Western countries, including the United States, Canada, and Germany. The reactions in France to his theories are less well-known. The purpose of this paper is to present an overview of critical responses to Singer by French academics and thinkers. How have they received Singer’s contention that we must bring nonhuman animals within the sphere of moral concern? How has his claim been received according to which we must recognize that the worth of human life varies? Do French scholars agree with his utilitarian views on abortion, euthanasia, infanticide, his de? nition of the term “person”? Finally, is he considered in France as a brilliant and groundbreaking ethicist, as a dangerous extremist, or somewhere in between